2017
DOI: 10.1002/app.45864
|View full text |Cite
|
Sign up to set email alerts
|

Effects of medium phases on the thermal degradation of hydrogenated nitrile rubber O‐rings under compression

Abstract: The degradation of hydrogenated nitrile rubber O‐rings under exposure to either air or hydraulic oil under compression were investigated at elevated temperatures. The physical and chemical changes of the samples aged for various durations were studied by measuring the weight, compression set, tensile strength, elongation at break, crosslinking density, fracture morphology, and attenuated total reflection–Fourier transform infrared (ATR–FTIR) spectroscopy. The results indicate that the weight decreased with exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…By comparing ATR‐FTIR spectra and the tensile test results, it appeared that the presence of unsaturated units enhanced oxidation via the CC bonds, which led to chain scissions, resulting in weak deformation resistance as observed for sample B13. Chaudhry et al observed the same phenomenon on HNBR as they showed a diminution of viscosity and M w of HNBR and concluded that degradation took place through chain scissions . Regarding the HNBR composition study, it has been proved that thermal crosslinking involves nitrile functions, like in PAN.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…By comparing ATR‐FTIR spectra and the tensile test results, it appeared that the presence of unsaturated units enhanced oxidation via the CC bonds, which led to chain scissions, resulting in weak deformation resistance as observed for sample B13. Chaudhry et al observed the same phenomenon on HNBR as they showed a diminution of viscosity and M w of HNBR and concluded that degradation took place through chain scissions . Regarding the HNBR composition study, it has been proved that thermal crosslinking involves nitrile functions, like in PAN.…”
Section: Resultsmentioning
confidence: 84%
“…Chaudhry et al observed the same phenomenon on HNBR as they showed a diminution of viscosity and M w of HNBR and concluded that degradation took place through chain scissions. 30,47 Regarding the HNBR composition study, it has been proved that thermal crosslinking involves nitrile functions, like in PAN. Moreover, a limit of this technique was highlighted when high butadiene content is present in HNBR.…”
Section: Effect Of Hnbr Compositionmentioning
confidence: 99%
“…Finally, the 500 ps NVT product run was conducted at 101 kPa and 298.15 K (25 °C), 343.15 K (70 °C), 363.15 K (90 °C), and 383.15 K (110 °C), respectively, to achieve the final stable structure. These temperatures were selected according to the accelerated test plans in our previous study [ 37 ]. Then, the equilibrated cells can be applied to analyze the FFV , MSD , self-diffusion coefficients, and diffusion trajectory to further investigate the effect of oxidative aging on the diffusion behaviors of the oxygen molecules and cyclohexane molecules in the unaged and aged nitrile rubber.…”
Section: Simulation Models and Methodsmentioning
confidence: 99%
“…The aging behavior of rubber products exposed to air and hydraulic oil at different temperatures was investigated using the accelerated aging test in our previous studies [ 36 , 37 ]. The thermal oxidative aging behavior and mechanism were deeply understood such as the chemical reactions (crosslinking and chain scission) and the formation of oxidation products.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies are found in the literature where accelerated aging has been applied to evaluate the degradation of rubbers. In many cases, the aim of the scientific research articles is to identify the behavior of the rubber over an extended period immersed in different corrosive environments such as hydraulic oil, [ 8,9 ] crude oil, [ 10 ] biodiesel, [ 11 ] aromatic fluid, [ 12,13 ] acid solutions, [ 14 ] or radioactive atmospheres. [ 15 ] Beside exposure to harsh environments, the recovery of elastomers after long‐term compression stresses is a target of various scientific investigations.…”
Section: Introductionmentioning
confidence: 99%